2019
DOI: 10.21608/zvjz.2019.14389.1056
|View full text |Cite
|
Sign up to set email alerts
|

Potential Curative Effect of Curcumin on Gastric Ulcer Induced by Piroxicam in Male Albino Rats

Abstract: This study intended to investigate the curative effect of curcumin on piroxicam-induced gastric ulcer in rats. Twenty-seven male albino rats were allocated into three similar groups (9 of each). The first group (G1) was the control, G2 received piroxicam (30 mg∕ kg BW.) to induce gastric ulcer and G3 received piroxicam (30 mg∕ kg BW.) and on the third day it received curcumin (200 mg ∕ kg BW.) orally for 21 day. At the end of the experiment, the rats were humanly euthazied and blood and serum samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…We can link these results with other studies, the role of Bryophyllum pinnatum leaf extract in healing acetic acid-induced chronic GU model in rats (Araugo et al, 2021) All study groups showed non-significant differences in the volume of gastric juice, which was still within the normal range compared to the normal control group. This result is in agreement with Ibrahim et al (2019), who revealed that the piroxicam-induced ulcer model in rats showed non-significant changes in the gastric juice volume.…”
Section: Discussionsupporting
confidence: 93%
“…We can link these results with other studies, the role of Bryophyllum pinnatum leaf extract in healing acetic acid-induced chronic GU model in rats (Araugo et al, 2021) All study groups showed non-significant differences in the volume of gastric juice, which was still within the normal range compared to the normal control group. This result is in agreement with Ibrahim et al (2019), who revealed that the piroxicam-induced ulcer model in rats showed non-significant changes in the gastric juice volume.…”
Section: Discussionsupporting
confidence: 93%
“…As presented in Table 4, piroxicam treatment triggered a significant rise in hepatic and renal serum biomarkers, such as creatinine, urea, uric acid, ALT, AST, and Alkaline phosphatase levels, in comparison to controls (P≤0.05). These findings were consistent with earlier researches [46][47][48] that indicated that piroxicam caused significant rise in markers of liver and kidney activity, lowered PG-E2 concentrations and stimulated oxidative stress.…”
Section: Accordingsupporting
confidence: 93%